Fructose-fed streptozotocin-injected rat: an alternative model for type 2 diabetes - Wilson, Rachel D.; Islam, Md. Shahidul (Pharmacological reports, 2012)
The main objective of the study was to develop an alternative non-genetic rat model for type 2 diabetes (T2D). Six-week-old male Sprague-Dawley rats (190.56±23.60 g) were randomly divided into six groups, namely: Normal Control (NC), Diabetic Control (DBC), Fructose-10 (FR10), Fructose-20 (FR20), Fructose-30 (FR30) and Fructose-40 (FR40) and were fed a normal rat pellet diet ad libitum for 2 weeks. During this period, the two control groups received normal drinking water whilst the fructose groups received 10, 20, 30 and 40% fructose in drinking water ad libitum, respectively. After two weeks of dietary manipulation, all groups except the NC group received a single injection (ip) of streptozotocin (STZ) (40mg/kg b.w.) dissolved in citrate buffer (pH 4.4). The NC group received only a vehicle buffer injection (ip). One week after the STZ injection, animals with non-fasting blood glucose levels > 300mg/dl were considered as diabetic. Three weeks after the STZ injection, the animals in FR20, FR30 and FR40 groups were eliminated from the study due to the severity of diabetes and the FR10 group was selected for the remainder of the 11 weeks experimental period. The significantly (p<0.05) higher fluid intake, blood glucose, serum lipids, liver glycogen, liver function enzymes and insulin resistance (HOMA-IR) and significantly (p<0.05) lower body weight, oral glucose tolerance, number of pancreatic β-cells and pancreatic β-cell functions (HOMA-β) of FR10 group demonstrate that the 10% fructose-fed followed by 40mg/kg of BW STZ injected rat can be a new and alternative model for T2D.